Multinational coordination required for conservation of over 90% of marine species. (6th September 2021) - Roberson, Leslie A.; Beyer, Hawthorne L.; O'Hara, Casey; Watson, James E. M.; Dunn, Daniel C.; Halpern, Benjamin S.; Klein, Carissa J.; Frazier, Melanie R.; Kuempel, Caitlin D.; Williams, Brooke; Grantham, Hedley S.; Montgomery, Jamie C.; et al.
Abstract: Marine species are declining at an unprecedented rate, catalyzing many nations to adopt conservation and management targets within their jurisdictions. However, marine species and the biophysical processes that sustain them are naive to international borders. An understanding of the prevalence of cross‐border species distributions is important for informing high‐level conservation strategies, such as bilateral or regional agreements. Here, we examined 28, 252 distribution maps to determine the number and locations of transboundary marine plants and animals. More than 90% of species have ranges spanning at least two jurisdictions, with 58% covering more than 10 jurisdictions. All jurisdictions have at least one transboundary species, with the highest concentrations of transboundary species in the USA, Australia, Indonesia, and the Areas Beyond National Jurisdiction. Distributions of mapped biodiversity indicate that overcoming the challenges of multinational governance is critical for a much wider suite of species than migratory megavertebrates and commercially exploited fish stocks—the groups that have received the vast majority of multinational management attention. To effectively protect marine biodiversity, international governance mechanisms (particularly those related to the Convention on Biological Diversity, the Convention on Migratory Species, and Regional Seas Organizations) must be expanded to promote multinational conservation planning, and complimented by a holistic governance framework for biodiversity beyond national jurisdiction. Abstract : An understanding of how species are distributed across political borders in the ocean is important for informing high‐level conservation strategies. We used 28, 252 marine species range maps to determine the number and locations of transboundary plant and animal species. More than 90% of mapped marine species have ranges spanning at least two jurisdictions, with 58% covering more than 10 jurisdictions. All jurisdictions have at least one transboundary species, with the highest concentrations of transboundary species in the United States, Australia, Indonesia, and the Areas Beyond National Jurisdiction.